Initiation of delayed hydride cracking in zirconium-2.5 niobium. - Rodgers, Douglas Keith. (University of Ottawa (Canada), 1992)
Delayed Hydride Cracking (DHC) occurs in Zr-2.5Nb when certain requirements are met. The mechanism of DHC consists of diffusion of hydrogen to a stress concentrator, such as a crack-tip, precipitation then fracture of a hydride at the crack-tip, and repetition of the process; the crack advances in steps. Incubation times, to the start of cracking and crack-tip hydride morphologies have been measured in pre-cracked cantilever beam specimens tested at applied K$\rm\sb I$'s up to 20 MPam$\sp{1/2}$ and temperatures ranging from 100 to 250$\sp\circ$C. The incubation time for DHC was found to vary inversely with DHC velocity. Contrary to previous research, the incubation time is highly variable, even for a given temperature and applied K$\rm\sb I,$ and the crack-tip hydride morphology is much more complicated than the simple model of a single hydride at a crack-tip.
Keywords: Engineering, Mechanical.